Blue Bloods: The Van Alen Legacy - Book 4 - De la Cruz, Melissa 1971- (New York : Disney/Hyperion, 2009)
Once left to live the glamorous life in New York City, the Blue Bloods--an ancient group of vampires--now find themselves in an epic battle for survival following the stunning revelation of a young socialite's true identity and the growing threat of the sinister Silver Bloods.
Accelerated Reader AR